Perceptions about the effectiveness of programme monitoring and evaluation rendered to Development Centres by the Department of Social Development in the Gauteng North Region. - Henna, Thembinkosi Elliot (My University, 2014)
Eradicating poverty is one of the biggest challenges in South Africa. A Development Centre Model was developed by the Department of Social Development as a strategy to empower citizens of South Africa to become independent and self-reliant in an attempt to alleviate poverty. The Department fulfils the role of programme monitoring and evaluation of different programmes offered by the Development Centres. A Social Development Approach was used as a guide to the theoretical framework of the study. The primary aim of the study was to explore the perceptions about the effectiveness of monitoring and evaluation of incomegenerating projects rendered to the development centres by the Department of Social Development in the Gauteng North Region. A qualitative research strategy was followed and a multiple case study design was applied. Purposive sampling was used to initially select six beneficiaries, six centre managers, two service providers and two departmental officials involved in the development centres that are government-funded. However, the total number of the participants in the end came to thirteen; five beneficiaries; five centre managers; two evaluators and one departmental official. Data was collected via face-to-face interviews with participants and the interviews were tape recorded. To analyse data, thematic content analysis was applied. Some of the findings and the recommendations are, firstly, that the study contributes to the understanding of the effectiveness of programme monitoring and evaluation; secondly, that programme monitoring and evaluation is in fact effective; and thirdly, that beneficiaries should participate in monitoring and evaluation of their projects. Fourthly, the majority of the beneficiaries and the centre managers felt that the process has no impact on the actual programme or projects. These participants felt that there is no follow-up to solve problems that have been identified during this process of monitoring and evaluation. The participants recommended that the department do more visits thereby making sure that problems identified during monitoring and evaluation are immediately resolved through constant visits to the development centres.
Keywords: Income-generating projects; Development Centres; Social Development; Developmental social welfare; Sustainable development